Exclusive moderate-dose radiotherapy in gastric marginal zone B-cell MALT lymphoma: Results of a prospective study with a long term follow-up. Issue 1 (October 2015) - Ruskoné-Fourmestraux, Agnès; Matysiak-Budnik, Tamara; Fabiani, Bettina; Cervera, Pascale; Brixi, Hedia; Le Malicot, Karine; Nion-Larmurier, Isabelle; Fléjou, Jean-Fançois; Hennequin, Christophe; Quéro, Laurent; ,
Abstract: Background: In gastric MALT lymphomas persisting after Helicobacter pylori ( H. pylori ) eradication, a treatment by moderate-dose radiotherapy (RT) has been proposed but its efficacy has not been confirmed in large prospective series with long term endoscopic follow-up. Method: Patients with localised gastric MALT lymphoma persisting after H. pylori eradication were offered moderate-dose RT (30 Gy, 2 Gy/fraction) and followed with annual endoscopies. All biopsies before and after RT were reviewed by a committee of pathologists. Results: From 1995 to 2011, out of the 232 patients followed prospectively, 53 received RT for persistence of lymphoma after H. pylori eradication: either macroscopic ulcer ( n  = 31), or microscopic lymphomatous infiltrate ( n  = 22), after a mean follow-up of 12 and 31 months, respectively. All lymphomas were localised (45 stage IE and 8 stage IIE) and 38 (72%) were H. pylori -positive. The mean clinical and endoscopic follow-up from diagnosis was 7.6 years (2.2–19.1). No acute or late toxicity occurred. A complete remission was achieved in all patients but one (98%) with no relapse after a median follow-up of 4.9 years (1.3–16.6) after completion of RT. Overall survival and 5-year disease specific survival were 94% and 100%, respectively. One patient died of gastric adenocarcinoma. Conclusion: Moderate-dose RT (30 Gy) is effective and safe for localised gastric MALT lymphoma persisting after H. pylori eradication.